A Drug Related Problems Research Phenomena in Pharmacy Journals in Indonesia: from Patient Criteria to DRPs Analysis - Tarigan, Missiary (Lembaga Berugak Baca, 2023)
The influence of Drug Related Problems on patient therapy is an issue that greatly affects the quality of life in the 21st century. This study analyzes a number of articles that have been published in pharmaceutical journals in Indonesia from 2010 to 2023, with Drug Related Problems as the main focus of the study. This study shows that in the last five years, the number of publications focusing on Drug Related Problems has decreased. Among these publications, the most common researcher is the Retrospective Observational Analysis Study. In addition, consecutive hospitalized patients were the object of the study, the DRPs classifications used were Cipolle, PCNE V 5, PCNE V 6.2, PCNE V 9.0, Pharmacology Handbooks, and many DRPs classifications were found to be 'not mentioned' in the literature used in the study. The DRPs research that was conducted was mostly conducted in Java Island while research in several other islands was very little found in Pharmaceutical Journals in Indonesia indexed by Sinta. In connection with the findings of this study, several recommendations have been proposed for future research that supports the analysis of Drug Related Problems on patient therapy as the main focus that can be seen from the results and discussion and conclusions.